Individual component analysis of gastrointestinal symptom rating scale for irritable bowel syndrome in irritable bowel syndrome patients treated with Bacillus coagulans SNZ 1969: additional findings from a randomized, double-blind, placebo-controlled study - P. V., Kishan; Soman, Raunak J.; Soman, Dhruv; Gorantla, Sarath Chandra (International Journal of Basic & Clinical Pharmacology, 2025)
This study evaluated the therapeutic efficacy of Bacillus coagulans SNZ 1969 (B. coagulans SNZ 1969) in patients with constipation-predominant irritable bowel syndrome (IBS-C) and diarrhea-predominant IBS (IBS-D). We conducted a randomized, double-blind, placebo-controlled trial in 80 patients (40 IBS-C, 40 IBS-D) who received either B. coagulans SNZ 1969 (500 million CFU) or placebo twice daily for 60 days. Assessments were performed at baseline and on days 30, 60, and 75. Here we present the additional findings of the individual components of Gastrointestinal Symptom Rating Scale for IBS (GSRS-IBS). Results demonstrated significant reductions in all individual components of GSRS-IBS (abdominal pain, bloating, constipation, diarrhea, and satiety) in both IBS-C and IBS-D patients treated with B. coagulans SNZ 1969 compared to placebo. In conclusion, B. coagulans SNZ 1969 found to be an effective therapeutic option for IBS, demonstrating broad efficacy across multiple symptom domains.